Real-Time Integration of PLC and ERP Odoo for Enhanced Production Monitoring Using OEE in a Bottle Sorting Plant - Asnawi, Mashudi; Agustina, Tri Siwi; Mustajib, Muhammad; Solakhudin, Muhammad Rafi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The integration of Operational Technology (OT) and Information Technology (IT) plays a pivotal role in optimizing enterprise-level decision-making, improving company efficiency and productivity. In this research, a software connector was designed to link Programmable Logic Controllers (PLCs) with Odoo’s Enterprise Resource Planning (ERP) system, facilitating real-time data acquisition from industrial machines. The integration supports communication protocols such as Modbus TCP/IP, Ethernet IP, and Profinet, enabling seamless data flow between OT and IT systems. To demonstrate this integration, a bottle sorting plant controlled by a PLC was developed, with production data transmitted in real-time to Odoo ERP. The Overall Equipment Effectiveness (OEE) method was employed within a custom-built manufacturing module in Odoo to monitor key performance metrics, including Availability, Performance, and Quality. Results of the OEE analysis were cross-verified with manual calculations, showing a 0% discrepancy, thus ensuring accuracy. In addition, the OEE metrics were visualized in Grafana, where real-time monitoring revealed the sorting machine's OEE at 85.7%, placing it in the world-class category. Availability reached 96.67%, Performance was at 92.53%, and Quality measured at 95.7%. This system not only streamlined production processes but also provided actionable insights, enabling the company to make data-driven improvements. The findings of this research highlight the benefits of IT-OT integration, improving machine performance and serving as a vital tool for evaluating production efficiency at the enterprise level.